1990
DOI: 10.1007/bf00404795
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus type 2-induced diabetes in mice prevented by immunosuppression and thymic hormone

Abstract: Reovirus type 2 that had been isolated from a cow with diarrhoea and passaged in bovine kidney cell culture produced a Type 1 (insulin-dependent) diabetes-like syndrome when inoculated into NC mice. The infection resulted in insulitis and destruction of islet cells. Viral antigens were found in islet cells by staining with fluorescein-labelled antibody to reovirus type 2. The destruction of islet cells resulted in abnormalities shown on glucose tolerance testing. Studies on the susceptibility of the host showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…In addition, reovirus types 1 and 2 were reported to cause autoimmune-related insulitis in mice (ONODERA et al 1978(ONODERA et al , 1981. Present study revealed that reovirus type 3 was pancreas-trophic.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, reovirus types 1 and 2 were reported to cause autoimmune-related insulitis in mice (ONODERA et al 1978(ONODERA et al , 1981. Present study revealed that reovirus type 3 was pancreas-trophic.…”
Section: Discussionmentioning
confidence: 51%
“…However, given that insulitis occurs in NOD mice infected with reovirus, we think it unlikely that passive tolerance alone explains the diabetes delay in these animals. Reovirus also can infect the murine pancreas (20,22,23), and our results suggest that reovirus is capable of infecting pancreatic ␤ cells in NOD mice (Fig. 1B and D).…”
mentioning
confidence: 80%
“…After passage in primary cultures of pancreatic ␤ cells, each of the three reovirus serotypes can infect the murine pancreas (20,22,23). Newborn SJL/J mice infected with reovirus develop an acute inflammatory response within pancreatic islets, and viral antigen can be detected by immunofluorescence in ␤ cells (20,23).…”
mentioning
confidence: 99%
“…1990). Most mice recovered from the disease within three weeks after infection (Onodera et al. 1990; Hayashi et al.…”
mentioning
confidence: 99%
“…1998, 2001). This may be due to the fact that a sufficient number of β‐cells were left intact after the destruction, and proliferation accompanied by disappearance of infiltrated cells may occur (Onodera et al. 1990).…”
mentioning
confidence: 99%